Formulation and Antioxidant Test of Soursop Leaf Lotion Preparation (Annona squamosa L.) Using the ABTS Method - Lisa Amalia; Tiara Ajeng Listyani; Danang Raharjo (International Journal of Health Engineering and Technology, 2026)
Soursop leaves (Annona squamosa L.) are known to contain secondary metabolite compounds such as flavonoids, alkaloids, tannins, and polyphenols that have the potential as natural antioxidants. Antioxidants play an important role in warding off free radicals that can cause skin damage, premature aging, and degenerative diseases. This study aims to formulate a lotion preparation with soursop leaf extract and evaluate its antioxidant activity using the ABTS (2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)) method. The extract was obtained through a maceration method using 96% ethanol. The lotion formula was prepared with various concentrations of soursop leaf extract, then tested for physical quality properties, as well as antioxidant activity by measuring the IC50 value of the ABTS radical solution. The results showed that soursop leaf extract has very strong antioxidant activity, indicated by a strong IC50 value. The resulting lotion preparation has good physical characteristics and antioxidant activity comparable to the comparator quercetin. Thus, soursop leaf extract lotion has the potential to be developed as a natural skin care product with moisturizing and antioxidant functions